Science communication for a sustainable academia: a comparative analysis of public and private universities Netherlands, Portugal, and Spain - Torres Mancera, Rocío; Martínez-Rodrigo, Estrella (European Public & Social Innovation Review, 2024)
Introduction: This research outlines a comprehensive study aimed at exploring the role of science communication in high education institutions, its impact and future sustainability in European universities across Netherlands, Portugal, and Spain. Methodology: By conducting a comparative review, we aim to provide valuable insights that can inform policy decisions and practices in the field of education sciences sharing knowledge in a more efficient manner. Through an examination of existing corporate data of public and private centers (N = 166) by conducting an exhaustive quantitative and correlational analysis of its official digital communications. Results: it is spotted that Spanish universities include more direct messages towards science communications, while Netherlands make much less general load but focuses more on sustainability topics. Findings suggests that in the stakeholder management, quantitative attempts in digital media are stronger from public institutions but may not be as decisive as the quality efforts, given that although Spain leads a higher gross value of online corporate communications, Dutch and Portuguese public universities are relatively much better valued in the global worldwide academic classification. Conclusions: This first study reveals an innovative unique new approach in cross-analyzing sustainable scientist knowledge, European universities, and international rating impacts based on the ARWU ranking.